Metabolomics study on the effects of Buchang Naoxintong capsules for treating cerebral ischemia in rats using UPLC-Q/TOF-MS. (2nd March 2016) - Liu, Mengting; Liu, Xin; Wang, Hongping; Xiao, Hongbin; Jing, Fang; Tang, Liying; Li, Defeng; Zhang, Yi; Wu, Hongwei; Yang, Hongjun
Abstract: Ethnopharmacological relevance: Buchang Naoxintong Capsules (BNC) are widely prescribed in Chinese medicine for the treatment of cerebrovascular and cardiovascular diseases. However, the therapeutic effects and mechanisms are not yet well understood. Materials and methods: In this study, a UPLC/TOF-MS-based metabolomic study was conducted to explore potential biomarkers that will increase our understanding of cerebral ischemia and to assess the integral efficacy of BNC in a middle cerebral artery occlusion (MCAO) rat model. Plasma metabolic profiles were analyzed and metabolic biomarkers were identified through multivariate data analysis. Results: Clear separations were observed between the sham, MCAO and BNC-treated groups. We identified 28 biomarkers in the MCAO rats using variable importance for the projections (VIP) values (VIP>1) and a t -test ( P <0.05). The identified biomarkers were mainly related to disturbances in monoamine neurotransmitter metabolism, amino acid metabolism, energy metabolism and lipid metabolism. Moreover, a correlation network diagram of the plasma biomarkers perturbed by MCAO was constructed. Some biomarkers, such as glutamine, PE (17:0), LysoPE (20:1), LysoPE (24:0), and the ratios of LysoPE (24:1) to LysoPE (24:0), LysoPE (24:2) to LysoPE (24:0), showed obvious changes and a tendency for returning to baseline values in BNC-treated MCAO rats. In addition, MCAO rats receiving BNC treatment had improved neurological deficits and reduced cerebral infarct size demonstrating the therapeutic potential of BNC for treating cerebral ischemia. Conclusion: This study provides a useful approach for exploring the mechanism of MCAO-induced cerebral ischemia and evaluating the efficacy of BNC. Graphical abstract: